1988
DOI: 10.1093/oxfordjournals.jbchem.a122554
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Protein Kinases in Membrane Fractions from Rat Cerebral Cortex1

Abstract: Specific activities of tyrosine tubulin kinase in the particulate fractions from rat cerebellum, medulla oblongata, hypothalamus, striatum, midbrain, and cerebral cortex ranged within 30% of each other and more than 3 times higher than those in the soluble fractions. In the cerebral cortex, tyrosine protein kinase activity toward tubulin and tyrosine-glutamate (1:4) copolymers was mainly distributed in the plasma membrane and the microsome fractions. The kinase activity in cerebral cortex particulate fractions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

1989
1989
1994
1994

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…In these controls the specific activity in the membrane fraction was more than three times higher than in the cytosolic fraction. Previously, comparable results were obtained for rat brain (Tsukamoto et al, 1988;Kobayashi et al, 1989).…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…In these controls the specific activity in the membrane fraction was more than three times higher than in the cytosolic fraction. Previously, comparable results were obtained for rat brain (Tsukamoto et al, 1988;Kobayashi et al, 1989).…”
Section: Discussionsupporting
confidence: 77%
“…Multiple autocrine loops involving receptors with associated PTK activities are present in human gliomas (Gammeltoft et al, 1988;Nister et al, 1988;Westphal and Hermann, 1989). In addition, it has been reported that the expression of c-src, yes, and fyn is high in normal human brain (Sudol and Hanafusa, 1986;Yamanashi et al, 1987;Tsukamoto et al, 1988). These findings prompted us to compare total PTK activities in normal brain and gliomas using a recently developed nonradioactive dot-blot assay .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations